2013
DOI: 10.1039/c3ra23348k
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and chemical composition of biomimetic calcium phosphate nanofibers

Abstract: a Calcium phosphate nanofibers with a diameter of only a few nanometers and a cotton-ball-like aggregate morphology have been reported several times in the literature. Although fiber formation seems reproducible in a variety of conditions, the crystal structure and chemical composition of the fibers have been elusive. Using scanning transmission electron microscopy, low dose electron (nano)diffraction, energy-dispersive X-ray spectroscopy, and energy-filtered transmission electron microscopy, we have assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…The film was compressed to 40 mN m −1 , and after 1–2 min, a 3 m phosphate solution was injected beneath the monolayer. For comparison with previous data mineralization was performed at 20 °C using 2 × 10 −3 m subphases. Moreover, the mineralization conditions were expanded to also include subphases with 20 and 200 × 10 −3 m and reaction times of 3, 4, and 5 h.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The film was compressed to 40 mN m −1 , and after 1–2 min, a 3 m phosphate solution was injected beneath the monolayer. For comparison with previous data mineralization was performed at 20 °C using 2 × 10 −3 m subphases. Moreover, the mineralization conditions were expanded to also include subphases with 20 and 200 × 10 −3 m and reaction times of 3, 4, and 5 h.…”
Section: Resultsmentioning
confidence: 99%
“…These morphologies are quite common for CP precipitated under biomimetic conditions. Needles, plates, and crumpled layers have been described before. Junginger et al mineralized CP beneath a basic block copolymer monolayer and found networks made of needles similar to our observation in Figures and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coated composites are usually prepared by electrochemically assisted co-deposition 154 or two-step biomimetic methods; 155,156 the mixed composites are fabricated via the 3D printing technique, 157 extrusion or direct injection into the bone defect site. Interestingly, the CaP-coated polymer nanober was recently fabricated by Junginger et al 158 via the mineralization process, and it is thought to add value to the synthesis of advanced hybrid materials for bone repair.…”
Section: Incorporating Cap With Polymersmentioning
confidence: 99%
“…[17][18][19] Only few studies address the effects of surfaces and interfaces on CP precipitation. 17,[19][20][21][22][23][24][25][26] There are also studies focusing on interface-controlled formation of other important (bio) minerals. 19,[27][28][29][30][31] The air-water interface is a useful model system to observe and quantify interface effects on CP formation.…”
Section: Introductionmentioning
confidence: 99%